Pengaruh Audit Fee, Komite Audit, dan Opini Audit Terhadap Terjadinya Auditor Switching Dengan Dimoderasi Oleh Reputasi Auditor - Aprilia Puspitawati; Muhsin Muhsin; Muhammad Fahmi (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
The objective of this study is to assess the degree to which the impact of audit fees, audit committees, and audit opinions on auditor switching is influenced by the reputation of the auditor. This study used quantitative techniques to investigate the impact of specific independent factors, namely audit fees, audit committees, and audit views, on the dependent variables of auditor switching and auditor reputation. Additionally, the study examined the role of auditor reputation as a moderating variable. This study utilises secondary data from all transport and logistics industry businesses that are publicly listed on the Indonesian stock market. The study sample comprises 84 analysis units and spans a research term of 3 years, namely from 2020 to 2022. The analytic tool used is WarpPLS version 8.0. The study findings indicate that audit fees have a substantial impact on the decision to switch auditors. However, the presence of an audit committee and the view expressed by auditors do not influence the decision to transfer auditors. The reputation of auditors does not have the ability to limit audit fees, audit committees, and audit opinions related to the switching of auditors.